Universality in consolidation of colloidal gels. Issue 47 (14th November 2016) - Roy, Saikat; Tirumkudulu, Mahesh S.
Abstract : The simulation snapshot on the left shows the consolidation of strongly-aggregated colloidal dispersion while the schematic on the right shows the structure of the particle network that contains flocs, which are formed by aggregation of particles. The correlation length of the flocs is identified as the end-to-end distance of chains, q . The shaded particles in the flocs are the elastically active particles in the chain that support stress. Abstract : Consolidation of colloidal dispersions under external load is a complex process involving inter-particle interactions, thermal forces and hydrodynamics. Despite its importance in diverse industrial applications, past studies involving experiments, scaling approaches and simulations are yet to provide a comprehensive understanding of how the microstructure determines the mechanical response in three dimensional colloidal gels. Here, we develop a model that accounts for the microstructural details and predicts the mechanical response under slow, uniaxial compression of a strongly aggregated three dimensional colloidal gel. The particle network assumes a fractal structure that is independent of the strength of inter-particle interactions. While the yield strain changes negligibly during the entire process, the yield stress increases by several orders of magnitude. The predicted yield stress and strain are in close agreement with those observed in simulations and experiments with diverse colloidal systems, suggesting a universality in the consolidation process.